2006
DOI: 10.1074/jbc.m602238200
|View full text |Cite
|
Sign up to set email alerts
|

Insoluble Aggregates and Protease-resistant Conformers of Prion Protein in Uninfected Human Brains

Abstract: Aggregated prion protein (PrPSc ), which is detergent-insoluble and partially proteinase K (PK)-resistant, constitutes the major component of infectious prions that cause a group of transmissible spongiform encephalopathies in animals and humans. PrP Sc derives from a detergent-soluble and PK-sensitive cellular prion protein (PrP C ) through an ␣-helix to ␤-sheet transition. This transition confers on the PrP Sc molecule unique physicochemical and biological properties, including insolubility in nondenaturing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
168
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 117 publications
(189 citation statements)
references
References 62 publications
19
168
0
2
Order By: Relevance
“…In this study, we also found that the previously described 18-kDa C1 PrP C fragment (44) shows a relatively high degree of protease resistance in white matter control samples. The observation that the C1 fragment has a higher PK resistance when compared with full-length PrP C has been already underlined in previous studies (52)(53)(54). We extended these observations and found that in white matter samples, the fragment is still detectable after PK digestion at an enzyme concentration of 20 units/ml, which is associated with a complete degradation of full-length PrP C .…”
Section: Discussionsupporting
confidence: 80%
“…In this study, we also found that the previously described 18-kDa C1 PrP C fragment (44) shows a relatively high degree of protease resistance in white matter control samples. The observation that the C1 fragment has a higher PK resistance when compared with full-length PrP C has been already underlined in previous studies (52)(53)(54). We extended these observations and found that in white matter samples, the fragment is still detectable after PK digestion at an enzyme concentration of 20 units/ml, which is associated with a complete degradation of full-length PrP C .…”
Section: Discussionsupporting
confidence: 80%
“…G5p is capable of capturing both rPrP Sc and PK-sensitive PrP Sc (sPrP Sc ) species. 14,20,21 Although the g5p beads precipitated the abnormal PrP Sc from 5 l of CJD brain homogenate, PrP was not detectable in samples captured by g5p from 6 ml of amniotic fluid and 6 ml of uterine and placental homogenates each in both CJD and non-CJD controls ( Figure 3B and data not shown). PrP was immunoprecipitable by 6H4-conjugated beads ( Figure 3B).…”
Section: Detection Of Prp In the Uterus Placenta And Amniotic Fluidmentioning
confidence: 90%
“…Anti-PrP antibodies, including rabbit anti-C-terminal antiserum immunoreactive to human PrP residues 220 to 231, mouse monoclonal antibody 3F4 against human PrP residues 109 to 112, mouse monoclonal antibody 1E4 against human PrP 97 to 108 (Cell Sciences, Canton, MA), and mouse monoclonal antibody 6H4 against human PrP 145 to 152 (Prionics AG, Zurich, Switzerland) were used. [11][12][13][14] Human Tissues Consent to use autopsy and biopsy material for research purposes was obtained for all samples. The neuropathological examination of biopsy and autopsy specimens of the proband was performed at the Indiana Alzheimer Disease Center, Indianapolis, IN, and at the National …”
Section: Reagents and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The types of protein that aggregate with the PrPreslike molecules are not known. Some plasma proteins are known to associate with the PrP, but it is possible that the PrP molecules in hamster plasma may also be a candidate for these plasma proteins (11,31,34). PK- resistant PrP molecules have recently been reported in uninfected human brains as well as in uninfected mouse and hamster brains and have been labeled a silent prion.…”
Section: Discussionmentioning
confidence: 99%